Evaluasi Kinerja Jalan Pada Jalur Kritis Jalan Temanggung Tilung (Sta 1+300 Sampai Sta 1+500): Evaluation of Road Performance on the Critical Route of Temanggung Tilung Road (Sta 1+300 to Sta 1+500) - Eli Suharti; Nirwana Puspasari (Media Ilmiah Teknik Sipil, 2023)
Temanggung Tilung road, a class 4/2 D road with 5.5-meter lanes, joins RTA Milono road and G. Obos road in Palangka Raya. This road sees more traffic every year. The research assessed the performance of Temanggung Tilung Palangkaraya sections during peak traffic hours and road section factors. Field surveys collected primary data. For performance analysis, it refers to the 1997 (MKJI) for urban roads and from the results of data processing, it shows that the degree of saturation that occurs is still optimal (DS = 0.22 pcu/hour) direction of G.Obos-RTA Milono while the direction of RTA Milono-G.obos with (DS = 0.22 pcu/hour) indicates that the road section is included in the standard class. Parameters on the Temanggung Tilung road section (existing) obtained the highest average traffic volume at peak hours on the Temanggung Tilung road section of 709.15 pcu/hour, the highest average speed of traffic space of 36.8 km/hour, the highest side resistance of 1026.43 side friction that occurs on the Temanggung Tilung road section is categorized as very high, both for parked or stopped vehicles, pedestrians and slow vehicles. Thus causing congestion at a certain point.